Using molecular dynamics for study butter - Ivanov, Sergey; Rashevska, Tamara; Shapoval, Victoria (My University, 2013)
With the help of program ChemBioUltra3D, the process of interaction between inulin polysaccharide and phosphatidylcholine (a type of phospholipid in lecithin) has been simulated. За допомогою програми ChemBioUltra3D було змодельовано процес взаємодії між полісахаридом інуліну та фосфатидилхоліном (тип фосфоліпідів у лецитині).
Keywords: butter; inulin; вершкове масло збагачене; інулін; кафедра технології молока і молочних продуктів; кафедра експертизи харчових продуктів